Enhancement of orthodontic tooth movement and root resorption in ovariectomized mice - Yasuhiko Nara; Hideki Kitaura; Aseel Marahleh; Fumitoshi Ohori; Takahiro Noguchi; Adya Pramusita; Ria Kinjo; Jinghan Ma; Kayoko Kanou; Itaru Mizoguchi (Elsevier, 2022)
Background/purpose: As the number of patients with osteoporosis requiring orthodontic treatment is increasing with the aging of society, it is necessary to evaluate the relations between bone metabolism in old age and orthodontic tooth movement (OTM). However, the effects of changes in bone metabolism due to osteoporosis on OTM and root resorption are still unclear. Therefore, we investigated the effects of OTM and root resorption in a mouse ovariectomy (OVX)-induced osteoporosis model. Materials and methods: Eight-week-old female wild-type mice underwent OVX or sham surgery (Sham) as controls. One month after treatment, a nickel titanium coil spring was used to apply a mesial force to the maxillary left first molars of OVX or Sham mice for 12 days. The distance between the maxillary first molar and the second molar changed due to OTM and osteoclast formation was evaluated. The odontoclast formation and root resorption along the root surface of the distobuccal root of the first molar was also evaluated by histological analysis and scanning electron microscopy. Results: Distance of tooth movement and osteoclast formation were significantly increased in OVX mice compared to Sham controls. Furthermore, root resorption in the mesial surface of the distal molars induced by orthodontic force was significantly increased in OVX mice. Conclusion: The amount of OTM was significantly increased, and the accompanying root resorption was also increased in OVX mice. Therefore, attention should be paid to the risk of root resorption associated with orthodontic treatment in patients with osteoporosis.